Optimizing Creative Economic Potential through Training Implementation - Sukarana, Murdiani; Abdi, Abdi; Syahrial, Syahrial (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This research explores the important role of support in designing programs and training as a key element in improving community welfare in the area. The focus is on the strategies undertaken to strengthen the capacity of local communities in managing and sustainably utilizing the resources found in Malenrang Beach, Panaikang Village, East Sinjai Regency. The results of this study provide an in-depth look at the importance of two-way dialogue between service providers and communities, the provision of up-to-date information, and needs-based training in the context of tourism destination development. As a result, this research provides an important contribution in efforts to advance the potential of the creative economy in the Malenrang Beach area, Panaikang Village, East Sinjai Regency.